Suicide in older people: Revisioning new approaches. (13th January 2016) - Deuter, Kate; Procter, Nicholas; Evans, David; Jaworski, Katrina
Abstract: This discussion paper identifies and examines several tensions inherent in traditional approaches to understanding older people's suicide. Predicted future increases in the absolute number of elderly suicides are subject to careful interpretation due to the underreporting of suicides in older age groups. Furthermore, a significant number of studies of older people's death by suicide examine risk factors or a combination of risk factors in retrospect only, while current approaches to suicide prevention in the elderly place disproportionate emphasis on the identification and treatment of depression. Taken together, such tensions give rise to a monologic view of research and practice, ultimately limiting our potential for understanding older people's experience of suicide and suicidal behaviour. New approaches are necessary if we are to move beyond the current narrow focus that prevails. Fresh thinking, which draws on older people's experience of attempting to die by suicide, might offer critical insight into socially‐constructed meanings attributed to suicide and suicidal behaviour by older people. Specifically, identification through research into the protective mechanisms that are relevant and available to older people who have been suicidal is urgently needed to effectively guide mental health nurses and health‐care professionals in therapeutic engagement and intervention.